CLINICAL FEATURES, DIAGNOSTIC SIGNIFICANCE, AND PROGNOSIS OF VITREORETINAL LYMPHOMA IN YOUNG PATIENTS. Issue 12 (December 2021) - Liu, Shixue; Gu, Junxiang; Zhang, Ting; Ping, Bo; Zhou, Min; Huang, Xin; Jiang, Rui; Xu, Gezhi; Chang, Qing
Abstract : Purpose: To investigate the clinical features, diagnostic approaches, and outcomes of young patients with vitreoretinal lymphoma. Methods: Fifty-one vitreoretinal lymphoma patients (97 eyes) referred to the Eye and ENT Hospital of the Fudan University from 2011 to 2020 were grouped based on their onset age (age ⩽50 years and age >50 years). Complete eye examinations, evaluation of systemic conditions, and biological analysis of intraocular fluids were performed. Results: Young patients accounted for 31.4% (n = 16) of the cohort. More eyes had retinal/subretinal pigment epithelial infiltration (20 [64.5%] vs. 23 [34.8%]; P = 0.018) in young patients than in elderly ones. The mutation rate of Myeloid Differentiation Factor 88 gene ( MYD88 ) was significantly lower in young patients than in elderly ones (5 [50%] vs. 21 [91.3%]; P = 0.016). The median time to new onset of central nervous system lymphoma was significantly shorter in young patients (11.7 vs. 36.2 months; P = 0.012). However, mean overall survival did not differ between the 2 groups (64.9 vs. 57.5 months; P = 0.871). Conclusion: Early diagnosis and central nervous system evaluation are crucial for young vitreoretinal lymphoma patients with rapid central nervous system involvement. Meanwhile, young vitreoretinal lymphoma patients have some unique features, including more retinal/subretinal pigment epithelial infiltrations and lower MYD88 mutation rates. Abstract : Young vitreoretinal lymphoma patients have lower mutation rates of the Myeloid Differentiation Factor 88 gene and a higher probability of retinal/subretinal pigment epithelial infiltration. Early diagnosis and systemic screening are essential because of potential earlier central nervous system involvement in young patients than in elderly patients.